2017
DOI: 10.4088/jcp.16r11083
|View full text |Cite
|
Sign up to set email alerts
|

Infant-Related Intrusive Thoughts of Harm in the Postpartum Period

Abstract: Fifty articles were included. The prevalence of harming intrusions is up to 100% in both women with and without psychiatric disorders. Stress and cognitive misinterpretation are important keys in its appearance and severity. Literature consistently states that isolated harming intrusions contain no increased risk of violence; instead, compulsive behavior is very common. Psychoeducation is found to release a lot of distress; so might cognitive-behavioral therapy and psychotropic medications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 0 publications
1
24
0
Order By: Relevance
“…None of the women in this study reported harsh or abusive behaviour towards the infant in response to IRHTs. This finding corroborates research consistently showing that ego-dystonic thoughts experienced postpartum do not reflect intention to harm, and therefore do not represent increased risk of violence (Brok et al, 2017;Fairbrother & Woody, 2008;Lawrence et al, 2017).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…None of the women in this study reported harsh or abusive behaviour towards the infant in response to IRHTs. This finding corroborates research consistently showing that ego-dystonic thoughts experienced postpartum do not reflect intention to harm, and therefore do not represent increased risk of violence (Brok et al, 2017;Fairbrother & Woody, 2008;Lawrence et al, 2017).…”
Section: Discussionsupporting
confidence: 88%
“…IRHTs have been associated with distress, guilt and shame, likely compounded by being poorly understood by healthcare professionals and little talked about generally (Brok et al, 2017;Lawrence et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These thoughts may include, for example, ideas of suffocation and sudden infant death syndrome (81.4–90%), accidents (83.7–92%), contamination (53.5–59%), or intentional harm (32.6–46%) [2, 3]. Such thoughts usually peak in frequency during the first few weeks postpartum [4]. Although women vary in how distressing they experience postpartum intrusive thoughts of infant-related harm to be, thoughts of intentional harm (i.e., harming the infant on purpose) have been found to be particularly upsetting [1, 5].…”
Section: Introductionmentioning
confidence: 99%
“…17 Mothers may hesitate to self-report intrusive thoughts of harm due to feelings of guilt, shame, or fear that voicing these thoughts will signify that they are a bad parent or trigger a report to CPS. 18 Even mothers who are not depressed may experience egodystonic aggressive thoughts or urges toward their infants, particularly if their infants cannot be soothed (eg, because of colic). 19 The source of the obsessional thoughts is critical, as OCD alone has not been shown to increase the risk of infanticide and, if anything, may decrease the risk.…”
Section: Discussionmentioning
confidence: 99%